2010
DOI: 10.1108/13217341011059381
|View full text |Cite
|
Sign up to set email alerts
|

The boycott model of foreign product purchase: an empirical test in China

Abstract: PurposeThe primary purpose of this paper is to investigate and ascertain the effects of integrative motivation on the willingness to participate in boycott activities.Design/methodology/approachThis paper uses a mail survey to examine the relationships among six constructs in a boycotting issue context, in order to explore Chinese consumers' willingness to boycott against Japanese products or services with the fallout from a Japanese former PM's continuous visits to a controversial war shrine since 2001.Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…ethnocentric tendencies and religiosity play a significant role in influencing animosity (Billiet, 1995;Karanovic et al, 2005) and between the two, ethnocentric tendencies influence more; and . animosity and product judgment play a significant role in influencing purchase behavior (Nijssen et al, 1999;Smith and Li, 2010) and between the two, product judgment influences more.…”
Section: Discussion and Marketing Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…ethnocentric tendencies and religiosity play a significant role in influencing animosity (Billiet, 1995;Karanovic et al, 2005) and between the two, ethnocentric tendencies influence more; and . animosity and product judgment play a significant role in influencing purchase behavior (Nijssen et al, 1999;Smith and Li, 2010) and between the two, product judgment influences more.…”
Section: Discussion and Marketing Implicationsmentioning
confidence: 99%
“…A study by Ettenson and Klein (2005) indicate that product judgment is predictive of prior purchase behavior(s). However, a recent study by Smith and Li (2010) on the boycott of Japanese products by Chinese consumers has shown that product judgment is linked to willingness to participate in product boycotts (purchase behavior). Based on these arguments, we hypothesize that:…”
Section: Relationship Between Religiosity and Ethnocentric Tendenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated that consumer animosity can directly influence consumers' willingness to buy (Witkowski, 2000;Hinck, 2005;Shoham et al, 2006;Ishii, 2009), or willingness to boycott (Nijssen and Douglas, 2004;Smith and Li, 2010). Some studies of consumer animosity have examined changes in animosity over time and discriminated between stable animosity and situational animosity (Jung et al, 2002).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Anti-consumption has been studied from many di erent perspectives and can take a lot of various forms (Iyer & Muncy, 2009;Zavestoski, 2002), such as boyco s (Albrecht et al, 2013;Farah & Newman, 2010;Friedman, 1985;John & Klein, 2003;Klein et al, 2004;Mrad et al, 2013;Smith & Li, 2010;Yuksel & Mryteza, 2009), ethical consumption (Carrigan & A alla, 2001; Ho mann & Hu er, 2012), brand avoidance (Kim et al, 2013;Lee et al, 2009a;Lee et al, 2009b;Rindell et al, 2013;ompson et al, 2006), voluntary simpli cation (Cherrier, 2009), brand rejection (Nenycziel & Romaniuk, 2011;Sandikci & Ekici, 2009;Truong et al, 2011), consumer resistance (Lee et al, 2011), anti-branding (Krishnamurthy & Kucuk, 2009), sharing (Ozanne & Ballantine, 2010), anti-consumption motivated by undesired-self and image congruency (Banister & Hogg, 2004;Englis & Solomon 1995;1997;Hogg et al, 2009;Sirgy, 1982). Some of these forms are more active, aggressive, and publicly noticeable while others are more passive and less noticeable.…”
Section: E Concept Of Brand Avoidancementioning
confidence: 99%